The EVA-based Performance Evaluation for Moutai in Nearly Three Years - Du, Wei; Jin, Yongxia; Zhang, Si (Global Disclosure of Economics and Business, 2014)
This paper calculated the EVA index of Moutai by the method of empirical analysis. We first compare the Eva index with other similar indices and then compare the indexes of Moutai with other enterprises’ indexes. Finally, the conclusion obtained is that Moutai has achieved outstanding performance in nearly three years. The company is still faced with many challenges in operations; we come up with some effective measures.JEL Classification Code: D04; D46